Achieving fully-equiaxed fine β-grains in titanium alloy produced by additive manufacturing. Issue 1 (2nd January 2023) - Xue, Aitang; Lin, Xin; Wang, Lilin; Lu, Xufei; Yuan, Lukai; Ding, Hanlin; Huang, Weidong
Abstract : The achievement of fine equiaxed β grain with conventional intragranular (α-Ti+β-Ti) microstructure in additive manufacturing titanium alloy remains a big challenge. We conquer this challenge by synergistically controlling β-grains during both solidification and subsequent thermal-cycles of laser directed energy deposition (DED), and a solution + quenching heat-treatment. Both the strength and plasticity of heat-treated Ti6Al4V3Ni0.05B are superior to those reported new DED titanium alloy and comparable to that of DED Ti6Al4V, because of the fine-equiaxed β-grains with intragranular (α-Ti+β-Ti) microstructure. These findings provide new insight into the grain structure control and the composition design of AM titanium alloy. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: The synergetic control of β-grain during both solidification and subsequent thermal-cycling is essential for achieving fully-equiaxed fine β-grains in additively manufactured titanium alloys.